2015
DOI: 10.1080/1064119x.2014.890986
|View full text |Cite
|
Sign up to set email alerts
|

Stability Study of a Tide Embankment Subjected to Sea Level Variations Using Centrifugal Model Tests

Abstract: To investigate the behavior of dredged-sea-sand fill compacted inside tide embankments with a damaged geosynthetic mat, centrifugal model tests and numerical simulation were conducted, both considering variations in sea level. The results from the three centrifugal model tests demonstrate that the subsidence of the dredged-sea-sand fill inside tide embankments with a damaged geosynthetic mat was strongly affected by the loss of dredged-sea-sand into the filter layers with large particles and a decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The complex formation process results in distinct stratification of the offshore and coastal soils, i.e., uneven mixing between coarse and fine particles. For example, the stratigraphical results from the Shetland Islands show distinct stratification of coarse and fine particles, which is confirmed to have been caused by three tsunamis between 8000 and 1500 years ago [5]; some artificial activities also create layered coastal foundations [6]. Previous studies have shown that the uniformity of mixing between particles affects the local and even the global properties of granular materials [7,8].…”
Section: Introductionmentioning
confidence: 91%
“…The complex formation process results in distinct stratification of the offshore and coastal soils, i.e., uneven mixing between coarse and fine particles. For example, the stratigraphical results from the Shetland Islands show distinct stratification of coarse and fine particles, which is confirmed to have been caused by three tsunamis between 8000 and 1500 years ago [5]; some artificial activities also create layered coastal foundations [6]. Previous studies have shown that the uniformity of mixing between particles affects the local and even the global properties of granular materials [7,8].…”
Section: Introductionmentioning
confidence: 91%
“…To define the behavioral characteristics of reservoir embankments, seismic-wave-charged dynamic centrifuge model tests were conducted to measure and analyze the earthquake response acceleration, displacement, and pore water pressure [4,5]. The acceleration amplification characteristics show that the amplification is large at the top.…”
Section: Extended Abstractmentioning
confidence: 99%